(untitled) (International Journal of Engineering and Computer Science, 2013)
Online Shopping Cart Access Control presents a new security concerns for cloud computing applications in general. Contemporarily, these solutions (Online Shopping Cart) now leverages on Cloud Computing Software as a Service, Platform as a Service, and infrastructure as a Service delivery models viz: Cloud Web Hosting,Cloud Hosting, Reseller Web Hosting, Business Web Hosting, Dedicated Instances, and Web Hosting Business solutions. Shopping Carts can now be dedicated to providing customers with the most reliabile web order as well as web hosting services in real time. Candidate models like X-cart, S-cart Now by Amazon Services,Cubecart,Zen Cart, aspdotnetstorefront,WDL and Mal’s E-commerce among others leverages on the potential benefits associated with today’s e-commerce. Most e-Commerce proposals in literature lacks adequate security integration and trust, making online transactions vulnerable at large. This paper presents ISCloud V.1.0, an interactive cloud shopping cart based SaaS with Hybrid Cryptography in which a fast high-quality symmetric-key and public key encryption algorithm is used for access authentication. In context, the generated symmetric key is used for integrity encryption for the authentication access in ISCloud V.1.0 SaaS model. For service trust by customers,a Secured Socket layer Certificate authority (domain validation) will be acquired from a trust Certificate Authority at its deployment. The design methodology and service framework is detailed in the body of this paper. PhP,XAMPP Apache and MySQL is used for a prototype implementation.